Influence of different fixation modes on biomechanical conduction of 3D printed prostheses for treating critical diaphyseal defects of lower limbs: A finite element study - Liu, Bingchuan; Lv, Yang; Li, Xingcai; Liu, Zhongjun; Zheng, Yufeng; Wen, Peng; Liu, Ning; Huo, Yaping; Zhou, Fang; Tian, Yun (Frontiers in Surgery, 2022)
Background: Applying 3D printed prostheses to repair diaphyseal defects of lower limbs has been clinically conducted in orthopedics. However, there is still no unified reference standard for which the prosthesis design and fixation mode are more conducive to appropriate biomechanical conduction. Methods: We built five different types of prosthesis designs and fixation modes, from Mode I to Mode V. Finite element analysis (FEA) was used to study and compare the mechanical environments of overall bone-prosthesis structure, and the maximum stress concentration were recorded. Additionally, by comparing the maximum von Mises stress of bone, intramedullary (IM) nail, screw, and prosthesis with their intrinsic yield strength, the risk of fixation failure was further clarified. Results: In the modes in which the prosthesis was fixed by an interlocking IM nail (Mode I and Mode IV), the stress mainly concentrated at the distal bone-prosthesis interface and the middle-distal region of nail. When a prosthesis with integrally printed IM nail and lateral wings was implanted (Mode II), the stress mainly concentrated at the bone-prosthesis junctional region. For cases with partially lateral defects, the prosthesis with integrally printed wings mainly played a role in reconstructing the structural integrity of bone, but had a weak role in sharing the stress conduction (Mode V). The maximum von Mises stress of both the proximal and distal tibia appeared in Mode III, which were 18.5 MPa and 47.1 MPa. The maximum peak stress shared by the prosthesis, screws and IM nails appeared in Mode II, III and I, which were 51.8 MPa, 87.2 MPa and 101.8 MPa, respectively. These peak stresses were all lower than the yield strength of the materials themselves. Thus, the bending and breakage of both bone and implants were unlikely to happen. Conclusion: For the application of 3D printed prostheses to repair diaphyseal defects, different fixation modes will lead to the change of biomechanical environment. Interlocking IM nail fixation is beneficial to uniform stress conduction, and conducive to new bone regeneration in the view of biomechanical point. All five modes we established have reliable biomechanical safety.